Graduate Unemployment in Ethiopia: the ‘Red Flag’ and Its Implications - Reda, Nigusse Weldemariam; Gebre-Eyesus, Mulugeta Tsegai (International Journal of African Higher Education, 2019)
The Ethiopian higher education sector has experienced a remarkable expansion in the past two decades. However, the accompanying trend of growing graduate unemployment appears to have been overlooked. This article examines graduate unemployment in Ethiopia using secondary data extracted from surveys conducted by the country’s Central Statistics Agency. While these statistics indicate that overall unemployment has decreased in Ethiopia, the percentage of graduate unemployment relative to total unemployment has increased. Moreover, unemployment among female graduates as compared to unemployed females is rising. It is thus timely for Ethiopia to undertake higher education reform aimed at aligning the expansion of the sector with market demand. Le secteur de l’enseignement supérieur en Ethiopie connaît un développement remarquable depuis deux décennies. Cela va cependant de pair avec un phénomène croissant de chômage chez les étudiants diplômés qui semble avoir été largement négligé. Cet article étudie le chômage chez les étudiants diplômés en Ethiopie, à partir de données secondaires qui proviennent d’enquêtes réalisées par l’Agence Centrale de Statistique (Central Statistics Agency) d’Ethiopie. Ces statistiques indiquent que, bien que le taux de chômage en Ethiopie ait baissé de façon globale, le pourcentage d’étudiants diplômés au chômage par rapport au nombre total de chômeurs a augmenté. De plus, le chômage chez les femmes diplômées connaît une augmentation par rapport au chômage chez les femmes de façon générale.